Compulsive buying and branding phenomena - Seung-hee Lee; Jane E. Workman (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
Background: The purpose of this paper was to explore the impact of brand variables such as brand awareness, brand loyalty, brand attachment, and perceived brand quality on compulsive buying behavior. Methods: A self-administered questionnaire, containing demographic items and items related to compulsive buying, brand awareness, brand loyalty, brand attachment and perceived quality, was used to collect data. Results: Participants were 269 US university students at a large mid-western university (138 men, 131 women; mean age = 21.96). Data were analyzed using descriptive statistics, t-test and MANOVA/ANOVA. Reliability of all scales was acceptable. In the current study, 18 % of the participants were classified as compulsive buyers. Women showed higher compulsive buying tendency than men. Participants with greater compulsive buying tendency scored higher on brand attachment and brand loyalty and lower on brand awareness; there was no difference in scores on perceived brand quality. Conclusions: Results support that brand variables such as brand awareness, brand loyalty, and brand attachment are related to compulsive buying behavior. New perceptions and implications for both academicians and practitioners are provided.
Keywords: 650; Compulsive buying; Brand awareness; Brand loyalty; Brand attachment; Perceived quality